Exploring Reproductive Health Education Needs and Barriers Among Adolescent Girls with Disabilities: A Qualitative Study - Agustini, Ni Komang Tri; Sagitarini, Putu Noviana; Diyu, Ida Ayu Ningrat Pangruating (Chakra Brahmanda Lentera Institute, 2026)
Background: Adolescents with disabilities remain among the most marginalized populations in accessing reproductive health services. Structural inaccessibility, social stigma, and limited awareness among health providers perpetuate inequities that compromise their reproductive rights and well-being. This study aims to explore the reproductive health service needs, experiences, and barriers faced by adolescents with disabilities to inform the development of inclusive and responsive reproductive health programs. Methods: A qualitative exploratory design was employed. Data were collected through in-depth interviews and focus group discussions with adolescents with various disabilities, their parents or caregivers, and key health workers. A total of 12 participants were purposively selected to represent diverse disability types and socio-demographic backgrounds. The Consolidated Criteria for Reporting Qualitative Research (COREQ) was applied in this research. Thematic analysis was conducted using an inductive coding approach to identify emerging patterns related to accessibility, service experience, and social attitudes. Results: Four interrelated themes emerged from the analysis: (1) Limited access and barriers to reproductive health information; (2) Sociocultural stigma and silences surrounding sexuality; (3) Unmet educational and emotional needs; (4) Strategies and aspirations for inclusive reproductive health education. This theme indicated that adolescent girl with disabilities face significant structural and information barriers that limit their ability to access accurate and accessible reproductive health information, thereby increasing their vulnerability to misinformation and unmet health needs. Conclusion: Adolescents with disabilities face multiple and intersecting barriers to accessing reproductive health services. Addressing these challenges requires systemic transformation through disability-sensitive training for health providers and a rights-based, inclusive education that reduces stigma and improves access.